Supporting supermom -- a needs and capacity assessment of mothers employed by a mid-sized midwestern corporation - McIlquham, Brittany (My University, 2011)
At times parenting can be a struggle, and its effects may bleed into other areas of a person's life, such as their work. Boundaries between a person's work life and family life have continued to fade in recent years. This makes finding a balance between the two, more difficult. According to the U.S. Census Bureau, in 2010, 21 percent of the U.S. workforce, or 33 million employees, were parents with children under the age of 18 years old (U.S. Census Bureau, 2010a; U.S. Department of Labor, 2011). Support for employed parents is needed from their family, friends, and maybe, most importantly, their employer (U.S. Office of Personnel Management, n.d.). The purpose of this research was to conduct a needs and capacity assessment of mothers employed by a mid-sized Midwestern corporation. Needs of the women and their capacity to meet them were evaluated with the use of key informant interviews and focus groups. The two biggest needs identified were flexibility in the workplace and consistency between departments and management. Capacity came in the form of proposed improvements in health promotion programming. Overall these working mothers felt they were not alone in trying to balance motherhood and the corporate work environment. Keywords: health promotion, wellness, employee wellness, worksite wellness, mothers, employees, needs assessment, capacity assessment.
Keywords: Work and family -- Middle West; Mothers -- Employment -- Middle West